A estética do poder - Passos, Álvaro Augusto dos (2010)
In all social organizations apart from their time and place, power relations are identified among their members or institutions. Family, religion, labour, education and above all the State, through its judicial order, influence the individuals motivating or inhibiting behaviors, aiming at making the coexistence of human beings satisfactory. This study intends to demonstrate the way the coexistence relations take place due to the appropriation of aesthetic signs as communication signals in order to convince that to act as settled is good